2019
DOI: 10.1177/0269881119862529
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y reduces expression of social fear via simultaneous activation of Y1 and Y2 receptors

Abstract: Background: Neuropeptide Y (NPY) has anxiolytic effects and facilitates extinction of cued and contextual fear in rodents, thereby acting as a resilience factor against exaggerated fear responses after adverse events. We investigated whether NPY influences acquisition, expression and extinction of social fear in a mouse model of social fear conditioning (SFC). Methods: NPY was administered intracerebroventricularly before SFC or before social fear extinction with or without prior administration of Y1 and/or Y2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Interestingly, all control SFC + mice (i.e., water-drinking and vehicle-treated) used in this study failed to show extinction of social fear, i.e., a gradual decrease in social fear as a result of repeated exposure to social stimuli. Gradual social fear extinction has been previously described in untreated and vehicle-treated CD1 mice [22,23,[34][35][36][37][38][39] and is similar to the outcome during exposure therapy in SAD patients [2]. This difference in social fear extinction might arise from potential genetic-related strain differences.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Interestingly, all control SFC + mice (i.e., water-drinking and vehicle-treated) used in this study failed to show extinction of social fear, i.e., a gradual decrease in social fear as a result of repeated exposure to social stimuli. Gradual social fear extinction has been previously described in untreated and vehicle-treated CD1 mice [22,23,[34][35][36][37][38][39] and is similar to the outcome during exposure therapy in SAD patients [2]. This difference in social fear extinction might arise from potential genetic-related strain differences.…”
Section: Discussionmentioning
confidence: 54%
“…These strain differences in social behavior were not only observed in SFC + mice but, also, in SFC − mice, i.e., SFC − ASM+/+, ASM+/−, and ASM−/− mice showed lower levels of social investigation during social fear extinction compared with SFC − CD1 mice. SFC − CD1 mice usually spend around 80% of the time investigating the social stimuli [22,23,[34][35][36][37][38][39] and show high levels of aggressive behavior, whereas SFC − C57BL/6 mice used in this study spent around 60% of the time investigating the social stimuli and showed no aggressive behavior.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations